2012
DOI: 10.2217/fon.12.122
|View full text |Cite
|
Sign up to set email alerts
|

HAMLET: Functional Properties and Therapeutic Potential

Abstract: Human α-lactalbumin made lethal to tumor cells (HAMLET) is the first member in a new family of protein-lipid complexes that kills tumor cells with high selectivity. The protein component of HAMLET is α-lactalbumin, which in its native state acts as a substrate specifier in the lactose synthase complex, thereby defining a function essential for the survival of lactating mammals. In addition, α-lactalbumin acquires tumoricidal activity after partial unfolding and binding to oleic acid. The lipid cofactor serves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 93 publications
(143 reference statements)
1
10
0
Order By: Relevance
“…The exact mechanism by which HAMLET-like complexes exert tumoricidal action continues to remain elusive despite concerted global efforts. Available data however suggest that the OA complex of α-LA selectively enters tumor cells and induces apoptosis-like events, stimulates macroautophagy and inhibits proteasomes [9,10]. Storm et al [11,12] using small-hairpin RNA inhibition, proteomic and metabolomics technologies showed that c-Myc oncogene is an important determinant of HAMLET sensitivity; cells expressing high levels of c-Myc were more sensitive, while knock down of the gene lowered HAMLET sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism by which HAMLET-like complexes exert tumoricidal action continues to remain elusive despite concerted global efforts. Available data however suggest that the OA complex of α-LA selectively enters tumor cells and induces apoptosis-like events, stimulates macroautophagy and inhibits proteasomes [9,10]. Storm et al [11,12] using small-hairpin RNA inhibition, proteomic and metabolomics technologies showed that c-Myc oncogene is an important determinant of HAMLET sensitivity; cells expressing high levels of c-Myc were more sensitive, while knock down of the gene lowered HAMLET sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, internalization of protein-lipid complexes to tumor cells, interference with proteasomes and perturbations of proteasome structure can combine with the cytotoxic activity of oxidized and misfolded protein complexes that attack the host cells. 95 f. Autophagic action Autophagy (autophagocytosis) is a natural pathway of orderly lysosomal degradation and recycling that has been used by eukaryotic cells to regulate large protein aggregates, intracellular organelles and dysfunctional components that cannot be degraded by proteasome cores. 96,97 In most eukaryotic cells, autophagy takes place at basal stages as an adaptive response in extreme cases such as starvation, which stimulates survival, but in other cases it appears to stimulate morbidity and cell death.…”
Section: Chromatin and Histones Interactionsmentioning
confidence: 99%
“…Since OA-protein complexes and GcMAF show no evidence of toxicity (Ho et al, 2012;Bradstreet et al, 2012), these complexes were selected as part of an integrative immunotherapeutic approach to advanced cancers in the context of the so-called compassionate approach. In this study we describe the preliminary experiences of treating patients with advanced cancers, some of them considered as "incurable", with an integrative immunotherapy centred on OA-GcMAF.…”
Section: Introductionmentioning
confidence: 99%